Incidental appendectomy during robotic laparoscopic prostatectomy - safe and worth to perform? - Hüttenbrink, Clemens; Hatiboglu, Gencay; Simpfendörfer, Tobias; Radtke, Jan Philipp; Becker, Roland Rainer Eberhard; Teber, Dogu; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus (Langenbeck's archives of surgery, 2018)
PurposeThe purpose of this study is to investigate the safety and patients’ benefit of incidental appendectomy during robot-assisted laparoscopic radical prostatectomy (RALRP).MethodsFifty-three patients, who had incidental appendectomy during RALRP between January 2012 and March 2014, were enrolled to this study. To evaluate the safety of the procedure, following parameters were evaluated: patient age, duration of surgery, perioperative complications (classified by Clavien-Dindo), time to bowel movement, and length of hospital stay. Furthermore, intraoperative visual appearance, location, and histopathological evaluation of the appendix were evaluated. Data was analyzed by descriptive statistics.ResultsMean age of patients was 61 years, the average hospital stay 5 days. No perioperative complications occurred. The appendix was unsuspicious in 39 patients (73.6%); 14 patients (26.4%) had macroscopically signs of inflammation.Of the 53 resected appendixes, the histopathological evaluation showed 33 (62.2%) inconspicuous appendices, 11 (20.8%) post-inflammatory changes, 4 (7.5%) with chronical signs of inflammation and 3 (5.7%) with signs of acute inflammation. In 2 patients (3.8%), low-grade mucinous neoplasms were found in the specimens.ConclusionsIncidental appendectomy during RALRP is a feasible procedure. With regard to inflammation and neoplastic changes, incidental appendectomy can be considered for patients scheduled for robot-assisted prostate surgery.